Editorial: aspirin and NSAID for chemoprevention of hepatocellular carcinoma – ready for their use? Authors' reply. Issue 6 (23rd August 2021) - Danta, Mark; Tan, Regina Zi Hwei; Lockart, Ian; Abdel Shaheed, Christina
LINKED CONTENT: This article is linked to Tan et al and Da Fonseca & Forner papers. To view these articles, visit https://doi.org/10.1111/apt.16515 and https://doi.org/10.1111/apt.16556